Blocking hsa_circ_0074027 suppressed non-small cell lung cancer chemoresistance via the miR-379-5p/IGF1 axis. Issue 1 (1st January 2021) - Zheng, Shizhen; Wang, Chao; Yan, Hao; Du, Yuejun
ABSTRACT: Cancer cell chemoresistance is the primary reason behind cancer treatment failure. Previous reports suggest that circular RNA (circRNA) hsa_circ_0074027 (HC0074027) is a crucial modulator of non-small cell lung cancer (NSCLC) disease progression. Herein, we delineated the underlying mechanism of HC0074027-regulated chemoresistance in NSCLC. We employed quantitative real-time polymerase chain reaction (qRT-PCR) or Elisa in the detection of HC0074027, micoRNA-379-5p (miR-379-5p), and insuline-like growth factor I (IGF1) expressions. Cell survival was evaluated via the 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT). Direct associations among HC0074027, miR-379-5p, and IGF1 were examined via dual-luciferase reporter (DLR) and RNA immunoprecipitation (RIP) assays. Lastly, HC0074027 was incorporated into nude mice to examine its biological activity in vivo . Based on our analysis, HC0074027 levels strongly correlated with NSCLC chemoresistance to docetaxel (DTX), cisplatin (DDP), and paclitaxel (PTX). Alternately, HC0074027 silencing enhanced chemosensitivity in vitro. In vivo, HC0074027 downregulation suppressed tumor expansion and increased cancer cell sensitivity to chemotherapy. We also revealed that HC0074027 physically interacts with miR-379-5p to exert its biological function in vitro . Moreover, IGF1 is a functionally crucial target of miR-379-5p in modulating NSCLC chemoresistance in vitro . Finally, we demonstrated that HC0074027 can indirectly modulate IGF1 levels via sequestering miR-379-5p. We demonstrated that HC0074027 promotes NSCLC chemoresistance via sequestering miR-379-5p activity, and modulating IGF1 expression. Our work highlights the significance of HC0074027 in NSCLC chemoresistance and suggests HC0074027 to be an excellent candidate for targeted NSCLC therapy.